2006
DOI: 10.1007/s11244-006-0042-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of catalyst film thickness on the electrochemical promotion of ethylene oxidation on Pt

Abstract: The effect of catalyst film thickness on the magnitude of the effect of electrochemical promotion of catalysis (EPOC or NEMCA effect) was investigated for the model catalytic reaction of C 2 H 4 oxidation on porous Pt paste catalyst-electrodes deposited on YSZ. It was found that the catalytic rate enhancement q is up to 400 for thinner (0.2 lm) Pt films (40,000% rate enhancement) and gradually decreases to 50 for thicker (1 lm) films. The results are in good qualitative agreement with model predictions describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…This phenomenon has been applied to numerous catalytic systems, 2 including treatment of automotive exhaust and oxidation of volatile organic compounds (VOCs). [5][6][7][8] Yttria-stabilized zirconia (YSZ) is one of the most studied solid electrolytes in EPOC catalytic systems and is known to be an O 2− conductor due to the presence of oxygen vacancies inside its crystallographic structure. Recently, it was found that EPOC effect, e.g.…”
mentioning
confidence: 99%
“…This phenomenon has been applied to numerous catalytic systems, 2 including treatment of automotive exhaust and oxidation of volatile organic compounds (VOCs). [5][6][7][8] Yttria-stabilized zirconia (YSZ) is one of the most studied solid electrolytes in EPOC catalytic systems and is known to be an O 2− conductor due to the presence of oxygen vacancies inside its crystallographic structure. Recently, it was found that EPOC effect, e.g.…”
mentioning
confidence: 99%
“…Λ values up to 3x10 5 and ρ values up to 150 (Vayenas et al, 2001) have been found for several systems. More recently ρ values between 300 (Koutsodontis et al, 2006a;2006b) and 1350 (Bebelis and Kotsionopoulos, 2006) have been measured for C 2 H 4 oxidation on Pt. In the experiment of Figure 2, Λ = 74,000 and ρ = 26, i.e.…”
Section: Electrochemical Promotion Of Catalysismentioning
confidence: 99%
“…Besides the results which have been already reported in the literature till 2001 and reviewed by Professor Vayenas et al in the ''Electrochemical Promotion of Catalysis'' book [28] several new studies have been reported till the end of 2008 using various techniques and methods such as TPD [29,30,32,47,72], TPR [29], CV [21], FTIR [21], SEM-EDX [21], AC impedance spectroscopy [39], STM [73,74], work function measurements and theoretical considerations [18,75,76], transients experiments and kinetic studies [34,35], quantum mechanical calculations and Monte Carlo simulations [77] and general thermodynamic considerations [18,78,79]. The use of oxygen temperature programmed desorption both under UHV and atmospheric pressure conditions has proven [29,30] the existence of two different and distinct oxygen adsorption states on the catalyst surface when oxygen ion conductors used like YSZ.…”
Section: Electrochemical Promotion Of Reactions With Environmental Anmentioning
confidence: 99%
“…A correlation between the behaviour of adsorbed oxygen species and the change in the selectivity of oxidative coupling of methane in SOFC reactor is also observed [91] be observed. Experimental validation for the above model came 5 years later by Koutsodontis et al [34,35] using several Pt/YSZ electrocatalysts with various Pt loadings, catalyst thickness and different methods of preparation. In these two studies the effect of catalyst film thickness on the magnitude of the effect of electrochemical promotion was investigated for the model catalytic reaction of C 2 H 4 oxidation.…”
Section: Electrochemical Promotion Of Reactions With Environmental Anmentioning
confidence: 99%
See 1 more Smart Citation